EFEK ANTIHIPERLIPIDEMIA EKSTRAK ETANOL BUAH STRAWBERRY (Fragraria x ananassa Duchesne) PADA TIKUS PUTIH DARI DAERAH BANDUNG - Nur Rahayuningsih; Tita Nofianti (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2015)
A study on triglycerides levels and total cholesterol activity in rats blood serum. This experiment use 42 rats, they were divided into 6 group . The first group was given by standart treatment of dietary  and aquadest, the second group was given by dietary of high fatty and aquadest, the third group was given by simvastatin suspension dose 0.9 mg /Kg BB, the four group, the five group and the six were orally given by of ethanolic extract strawberry fruit with dose 0.21 gram/kgBB; 0,425 gram/kgBB; and 0.85 gram/kgBB. Hyperlipidemia was treated with high dietary fatty (profiltiourasil 9 mg /kgBB and egg yolk 10 ml/Kg BB). The triglycerides, total cholesterol, LDL-cholesterol and HDL-cholesterol levels content determined with GPO (Glycerol-3-Phosphate Oxidase) test. The result of the research showed that ethanolic extract strawberry fruit 2 weeks can decrease triglycerides, total cholesterol,  LDL-cholesterol and increased HDL-cholesterol levels. Keywords: strawberry fruit, triglycerides, cholesterol total, LDL-cholesterol and HDL-cholesterol.